PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI, PROFESIONALISME, GAYA KEPEMIMPINAN, DAN STRUKTUR ORGANISASI TERHADAP KINERJA MANAJERIAL - Badu, Irman; Awaluddin, Ishak; Mas'ud, Arifuddin (JPEP (Jurnal Progres Ekonomi Pembangunan), 2019)
This study aims to determine the Effect of Budgetary Participation, Organizational Commitment, Professionalism, Leadership Style and Organizational Structure on Managerial Performance of Kendari City Government. This research is a causality research and the object of research is 32 OPD of Kendari City Government. Data collection techniques are done by distributing questionnaires, interviews and collecting documentation. The sample in this study were 139 respondents. Analysis of the data used in this study is a multiple regression analysis method that is processed through AMOS SPSS 22 software. Based on the results of statistical calculations, it shows that jointly budgeting participation, organizational commitment, professionalism, leadership style and organizational structure towards managerial performance of Kendari City Government have a positive and significant effect, the partial effect of positive and significant budgeting participation on managerial performance of Kendari City Government , partial influence Organizational commitment has a positive and significant effect on managerial performance of Kendari City Government, partially professionalism towards managerial performance of Kendari City Government has a positive and significant effect, partially leadership style towards managerial performance of Kendari City Government has a positive and significant effect. Beta standardize value is negative with a value of 0.053 indicating that the partial effect of positive and significant leadership style on managerial performance of Kendari City Government and partially organizational structure on managerial performance of Kendari City Government has a positive and significant effect.Â Keywords: Budget Formation Participation, Organizational Commitment, Professionalism, Leadership Style, Organizational Structure, Managerial Performance